Elevated plasma factor VIII enhances venous thrombus formation in rabbits: Contribution of factor XI, von Willebrand factor and tissue factor - Sugita, Chihiro; Yamashita, Atsushi; Matsuura, Yunosuke; Iwakiri, Takashi; Okuyama, Nozomi; Matsuda, Shuntaro; Matsumoto, Tomoko; Inoue, Osamu; Harada, Aya; Kitazawa, Takehisa; Hattori, Kunihiro; Shima, Midori; Asada, Yujiro (Thrombosis and Haemostasis, 2013)
Elevated plasma levels of factor VIII (FVIII) are associated with increased risk of deep venous thrombosis. The aim of this study is to elucidate how elevated FVIII levels affect venous thrombus formation and propagation in vivo. We examined rabbit plasma FVIII activity, plasma thrombin generation, whole blood coagulation, platelet aggregation and venous wall thrombogenicity before and one hour after an intravenous infusion of recombinant human FVIII (rFVIII). Venous thrombus induced by the endothelial denudation of rabbit jugular veins was histologically assessed. Thrombus propagation was evaluated as indocyanine green fluorescence intensity. Argatroban, a thrombin inhibitor, and neutralised antibodies for tissue factor (TF), factor XI (FXI), and von Willebrand factor (VWF) were infused before or after thrombus induction to investigate their effects on venous thrombus formation or propagation. Recombinant FVIII (100 IU/kg) increased rabbit plasma FVIII activity two-fold and significantly enhanced whole blood coagulation and total plasma thrombin generation, but did not affect initial thrombin generation time, platelet aggregation and venous wall thrombogenicity. The rFVIII infusion also increased the size of venous thrombus 1 hour after thrombus induction. Argatroban and the antibodies for TF, FXI or VWF inhibited such enhanced thrombus formation and all except TF suppressed thrombus propagation. In conclusion, elevated plasma FVIII levels enhance venous thrombus formation and propagation. Excess thrombin generation by FXI and VWF-mediated FVIII recruitment appear to contribute to the growth of FVIII-driven venous thrombus.
Keywords: Deep venous thrombosis; factor VIII; factor XI; von Willebrand factor